Accuracy analysis of geometrical and numerical approaches for two degrees of freedom robot manipulator - Saputra, Hendri Maja; Mirdanies, Midriem; Rijanto, Estiko (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2016)
Analysis of algorithms to determine the accuracy of aiming direction using two inverse kinematic approaches i.e. geometric and numeric has been done. The best method needs to be specified to precisely and accurately control the aiming direction of a two degrees of freedom (TDOF) manipulator. The manipulator degrees of freedom are azimuth (Az) and elevation (El) angles. A program has been made using C language to implement the algorithm. Analysis of the two algorithms was done using statistical approach and circular error probable (CEP). The research proves that accuracy percentage of numerical method is better than geometrical method, those are 98.63% and 98.55%, respectively. Based on the experiment results, the numerical approach is the right algorithm to be applied in the TDOF robot manipulator.